Assessment of Triglyceride and Cholesterol Levels for a Sample of Type One Diabetic Patients - Aziza, Mohammed Mohsin; Alia, Safaa Hussein; Al-Ghareebawia, Aamir M. Abed (American Journal of Biology and Natural Sciences, 2024)
Diabetes is a medical condition that occurs routinely and can cause severe damage and long-term complications, such as kidney failure, blindness, end-organ necrosis, and amputation. The principal of this investigation was to determine the risk factors of long-term complications in Type 1 diabetics and the relationship between elevated levels of blood glucose, cholesterol, and triglycerides. The study had between 30 individuals divided into six groups by age and was conducted by comparing the patient's groups (A, B, C, D, and E) with the control group (N). The study attempted to examine three biochemical parameters: patients’ random blood sugar (RBS), cholesterol, triglyceride levels in the blood. The results help improve lifestyle, diabetic management, and nutritional-related actions. According to this examination, there were considerable differences between the control group and the patient's groups. The findings confirm a significant relationship between cholesterol, glucose, and triglycerides, and also conformed to the scientific guidance of lifestyle, diabetic management, and dietary preferences.